Process for improving the bonding strength of stainless steel shroud to the leading edge of a lifting blade
Patent Information
- Application Number
- CN202611152038.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]针对上述问题,本发明的目的在于提供一种提升桨叶前缘不锈钢包片胶接强度的工艺方法,旨在解决现有直升机复合材料桨叶前缘不锈钢金属包片与基体粘结强度不足、极易开胶,进而引发飞行安全隐患、抬高维护成本、缩短部件使用寿命的技术难题
[0037]本发明提供的一种提升桨叶前缘不锈钢包片胶接强度的工艺方法,融合不锈钢包片表面微结构设计与化学腐蚀技术,通过表面改性处理,改善不锈钢包片表面润湿性能,优化其胶接性能,显著增强不锈钢包片与桨叶基体的粘结强度,有效解决桨叶在恶劣环境或旋翼高速运转工况下,不锈钢包片易脱离基体的技术难题。该项技术不仅可以缩短桨叶维护时间,降低维护成本,还能提升桨叶的使用寿命与直升机的综合性能,具有显著的工程应用效益与技术优化价值。
Smart Images

Figure CN122956726A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of blade manufacturing technology, and specifically relates to a process method for improving the bonding strength of stainless steel cladding on the leading edge of blades. Background Technology
[0002] In the technological development of helicopters, the rotor blades, as the core load-bearing components, directly determine flight safety, load capacity, and service life. As helicopters evolve towards greater intelligence, higher speed, and heavier weight, the strength of the rotor blades remains at the forefront of technological innovation. The cladding, as the core protective element of the rotor blade components in aerospace transportation equipment, plays a crucial role in the flight safety and service life of helicopters due to its bonding performance with the blade substrate.
[0003] Currently, common metal surface treatment methods include mechanical treatment, laser etching, and electrochemical treatment. Mechanical treatment, such as sandblasting and polishing, can only change the roughness of the metal surface and cannot control the surface chemical composition, resulting in limited improvement in wettability; laser etching equipment is expensive, and its effectiveness may decrease over time; electrochemical treatment is more complex, has higher energy consumption costs, and requires continuous power supply.
[0004] In existing patent literature, publication number CN112846674A, entitled "A Method for Processing Titanium Alloy Edge Covering of Helicopter Blades," describes the following surface treatment for the titanium alloy edge covering of helicopter blades: sandblasting is performed on the titanium alloy surface during pretreatment; then, the sandblasted titanium alloy sheet is acid-washed to remove surface oil and other contaminants; after thermoforming, alkaline chipping and a second acid wash are performed; then, the titanium alloy edge covering is anodized; and finally, it is bonded and cured. This patented solution uses a composite process of sandblasting, multi-stage acid-alkali cleaning, and anodizing to treat the titanium alloy edge covering. It relies solely on roughness and the oxide layer to improve bonding safety, but it does not prefabricate a mesh microstructure on the surface of the edge covering, thus failing to form a three-dimensional mechanical interlocking structure and making it difficult to fundamentally solve the problem of easy delamination of the edge covering. Summary of the Invention
[0005] To address the aforementioned problems, the present invention aims to provide a process method for improving the bonding strength of stainless steel cladding at the leading edge of rotor blades. This method is intended to solve the technical challenges of insufficient bonding strength between the existing stainless steel cladding at the leading edge of helicopter composite rotor blades and the substrate, which easily leads to delamination, thereby causing flight safety hazards, increasing maintenance costs, and shortening the service life of components.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] This invention provides a process for improving the bonding strength of stainless steel cladding on the leading edge of a propeller blade, comprising the following steps:
[0008] Step S1: Prepare microstructured grooves on the surface of stainless steel sheet;
[0009] Step S2, billet pretreatment and partitioned film formation: the stainless steel sheet is polished, and then an acid-resistant organic protective film is prepared on the upper side of the microstructure groove and the rest of the surface of the stainless steel sheet, exposing the lower side of the microstructure groove.
[0010] Step S3, First chemical treatment: After cleaning and drying, selective corrosion is carried out using hydrochloric acid etching solution to form a deep corrosion area on the lower side of the microstructure tank.
[0011] Step S4, Second Chemical Treatment: A mixed etching solution is used for secondary etching treatment to remove the organic protective film on the surface of the stainless steel plate.
[0012] Step S5, Final Cleaning: Ultrasonic cleaning with a combination of organic solvents and drying are used to obtain a stainless steel sheet with a microstructure groove with secondary chemical corrosion.
[0013] Step S6, Vacuum bonding: The stainless steel sheet is pre-formed twice with different curvatures to store elastic potential energy. Two-component adhesive is applied to the bonding surfaces of the stainless steel sheet and the carbon fiber blade in a vacuum environment. The sheets are then elastically reset, tightly bonded and cured to form a spatial T-shaped locking bonding structure.
[0014] In step S1, the microstructure grooves on the bonding surface of the stainless steel sheet are square array mesh microstructures, the depth of the mesh microstructure is 0.1-0.4mm, the side length of a single square mesh is 0.3-0.6mm, and the mesh spacing is 0.1-0.2mm;
[0015] The mesh microstructure is formed by rolling with upper and lower paired molds. The bottom of the upper mold is provided with a square array of bosses, and the lower mold supports the stainless steel plate.
[0016] In step S2, the partitioned film formation process prepares an organic protective film resistant to hydrochloric acid through a photoreaction-enhanced film formation process; the organic protective film is an organosilicon-modified photocurable corrosion-resistant film, an epoxy acrylic photocurable composite film, a nano-doped photocurable organic composite film, or a photoinitiated grafted fluorine-containing organic film.
[0017] In step S3, the first chemical treatment process includes the following steps:
[0018] Step S31, Degreasing and Cleaning: After the stainless steel sheet has been divided into sections and film-forming, it is ultrasonically cleaned with acetone and anhydrous ethanol for 5-15 minutes in sequence; after cleaning, it is placed in an electric heating constant temperature drying oven to dry at a temperature of 70±5℃.
[0019] Step S32: Prepare a hydrochloric acid etching solution containing hydrochloric acid and ferric chloride;
[0020] Step S33, Chemical corrosion treatment: Immerse the degreased and dried stainless steel sheet in hydrochloric acid corrosion solution for corrosion. The corrosion temperature is controlled at 20-40℃ and the corrosion time is 100-300min. After corrosion treatment, directional deep corrosion occurs on the lower side of the microstructure groove of the stainless steel sheet along the direction perpendicular to the wall thickness.
[0021] In step S32, a hydrochloric acid etching solution containing hydrochloric acid and ferric chloride is prepared. The hydrochloric acid with a concentration of 36%-38% is selected, and the amount of hydrochloric acid added is 20-100 mL / L; the amount of ferric chloride added is 100-250 g / L.
[0022] In step S4, the second chemical treatment process includes the following steps:
[0023] Step S41, Cleaning and Drying: Use acetone and anhydrous ethanol in sequence to ultrasonically clean the stainless steel plate after the first chemical treatment process for 5-15 minutes, and dry it at 70±5℃.
[0024] Step S42: Prepare a mixed etching solution containing chromium trioxide and sulfuric acid;
[0025] Step S43, Secondary Corrosion: Immerse the stainless steel sheet after the first chemical treatment in the mixed corrosion solution and corrode it at 30-70℃ for 15-35 minutes.
[0026] In step S42, a mixed etching solution containing chromium trioxide and sulfuric acid is prepared. Concentrated sulfuric acid with a concentration of 98% is selected and added at a rate of 150-400 mL / L. The amount of chromium trioxide added is 100-300 g / L.
[0027] In step S5, the stainless steel sheet after the second chemical treatment process is ultrasonically cleaned for 5-15 minutes using acetone and anhydrous ethanol in sequence; after cleaning, the stainless steel sheet is placed in an electric heating constant temperature drying oven to dry, and the drying temperature is controlled at 70±5℃.
[0028] In step S6, the vacuum bonding includes the following steps:
[0029] Step S61: Perform the first preforming on the stainless steel cladding sheet that has been prepared with microstructured grooves through two chemical etching processes, so that the curvature of the stainless steel cladding sheet is less than the curvature of the surface to which the blade is bonded.
[0030] Step S62: Perform a second pre-forming on the stainless steel sheet. After forming, the curvature of the stainless steel sheet is greater than the curvature of the surface to which the blade is bonded. The stainless steel sheet is fixed by a vacuum chamber fixing fixture, and two welding pillars are welded to both sides of the outer surface. The two welding pillars are clamped by a vacuum motion fixture, so that the stainless steel sheet stores elastic potential energy.
[0031] Step S63: The vacuum coating robot applies adhesive A to the surface of the stainless steel sheet with chemically etched microstructure grooves in a vacuum environment.
[0032] Step S64: Another vacuum coating robot applies adhesive B to the surface of the blade to be bonded in a vacuum environment;
[0033] Step S65: The vacuum handling robot drives the blade displacement. The vacuum motion fixture drives the stainless steel sheet to move in space through two welded columns, releasing part of the elastic potential energy stored in the stainless steel sheet in advance, and completing the docking and bonding of the stainless steel sheet and the blade in a vacuum atmosphere.
[0034] Step S66: Keep the mixture warm and allow it to stand to fully cure the AB adhesive.
[0035] Step S67: Unload the material and remove the two welded pillars used for process clamping.
[0036] The present invention has the following beneficial effects and advantages:
[0037] This invention provides a process for improving the bonding strength of stainless steel cladding on the leading edge of rotor blades. It integrates microstructure design of the stainless steel cladding surface with chemical corrosion technology. Through surface modification treatment, the wettability of the stainless steel cladding surface is improved, optimizing its bonding performance and significantly enhancing the adhesion strength between the stainless steel cladding and the rotor blade substrate. This effectively solves the technical problem of stainless steel cladding easily detaching from the substrate under harsh environments or high-speed rotor operation. This technology not only shortens rotor blade maintenance time and reduces maintenance costs, but also improves rotor blade life and the overall performance of the helicopter, demonstrating significant engineering application benefits and technological optimization value.
[0038] Other features and advantages of the invention will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention may be realized and obtained by means of the structures particularly pointed out in the written description and the accompanying drawings.
[0039] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0040] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings:
[0041] Figure 1 This is a schematic diagram of the structure of a stainless steel pre-treated plate with microstructure grooves in an embodiment of the present invention;
[0042] Figure 2This is a side view of a stainless steel chemically etched sheet in an embodiment of the present invention;
[0043] Figure 3 This is an isometric view of a stainless steel chemically corroded sheet in an embodiment of the present invention;
[0044] Figure 4 This is a schematic diagram of the process of vacuum bonding stainless steel sheet to blade in an embodiment of the present invention;
[0045] Figure 5 This is an isometric view of the vacuum bonding structure between the stainless steel cladding and the blade in an embodiment of the present invention;
[0046] Figure 6 This is one of the exploded views of the vacuum bonding structure between the stainless steel cladding and the propeller blade in an embodiment of the present invention;
[0047] Figure 7 This is the second exploded view of the vacuum bonding structure between the stainless steel cladding and the blade in an embodiment of the present invention;
[0048] Figure 8 The following are experimental diagrams of the contact angle between stainless steel plates with different surface morphologies and liquids in embodiments of the present invention: (a) original smooth flat sample, (b) microstructure sample with a groove width of 0.1 mm, (c) microstructure sample with a groove width of 0.2 mm, (d) microstructure sample with a groove width of 0.1 mm after chemical etching, and (e) microstructure sample with a groove width of 0.2 mm after chemical etching.
[0049] In the figure: 1. Stainless steel pretreated plate; 101. Side; 102. Joint surface; 103. Bottom of microstructure groove; 104. Upper side of microstructure groove; 105. Lower side of microstructure groove; 2. Stainless steel chemically etched plate; 201. Side of etched material; 202. Joint surface of etched material; 203. Bottom of microstructure groove of etched material; 204. Upper side of microstructure groove of etched material; 205. Lower side of microstructure groove of etched material; 3. Adhesive layer; 4. Paddle; 5. Vacuum cavity fixing fixture; 6. First welding column; 7. Second welding column; 8. Stainless steel cladding. Detailed Implementation
[0050] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0051] The preferred embodiments of the present invention will be described below with reference to the accompanying drawings. It should be understood that the preferred embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0052] This invention provides a process for improving the bonding strength of stainless steel cladding on the leading edge of a propeller blade, comprising the following steps:
[0053] Step S1: Prepare microstructured grooves on the surface of stainless steel sheet;
[0054] Step S2, billet pretreatment and partitioned film formation: the stainless steel sheet is polished, and then an acid-resistant organic protective film is prepared on the upper side of the microstructure groove and the rest of the surface of the stainless steel sheet, exposing the lower side of the microstructure groove.
[0055] Step S3, First chemical treatment: After cleaning and drying, selective corrosion is carried out using hydrochloric acid etching solution to form a deep corrosion area on the lower side of the microstructure tank.
[0056] Step S4, Second Chemical Treatment: A mixed etching solution is used for secondary etching treatment to remove the organic protective film on the surface of the stainless steel plate.
[0057] Step S5, Final Cleaning: Ultrasonic cleaning with a combination of organic solvents and drying are used to obtain a stainless steel sheet with a microstructure groove with secondary chemical corrosion.
[0058] Step S6, Vacuum bonding: The stainless steel sheet is pre-formed twice with different curvatures to store elastic potential energy. Two-component adhesive is applied to the bonding surfaces of the stainless steel sheet and the carbon fiber blade in a vacuum environment. The sheets are then elastically reset, tightly bonded and cured to form a spatial T-shaped locking bonding structure.
[0059] Specifically, the selected two-component adhesive is preferably, but not limited to, Alomada AV138 / HV998 epoxy AB adhesive. This adhesive has the following core characteristics: low volatility, curing at a low temperature of 5°C, and a shear strength of up to 20 MPa; it is suitable for bonding metal and carbon fiber materials in special electronic communications and aerospace fields, and also has corrosion resistance and high temperature resistance.
[0060] In step S1, the microstructure grooves on the bonding surface of the stainless steel sheet are square array mesh microstructures, the depth of the mesh microstructure is 0.1-0.4mm, the side length of a single square mesh is 0.3-0.6mm, and the mesh spacing is 0.1-0.2mm;
[0061] The mesh microstructure is formed by rolling with upper and lower paired molds. The bottom of the upper mold is provided with a square array of bosses, and the lower mold supports the stainless steel plate.
[0062] In step S2, the pretreatment process of the billet is as follows: the stainless steel sheet to be treated is processed to the target size by wire cutting; then mechanical polishing or electrolytic polishing is carried out to make the surface of the billet flat and smooth, so as to provide a stable base condition for subsequent surface modification treatment.
[0063] Mechanical polishing process: Wet grinding is carried out sequentially using 600#, 800#, 1200# and 2000# sandpaper, followed by mirror polishing with 1-3μm diamond polishing paste. After treatment, the surface roughness of the workpiece meets Ra≤0.4μm.
[0064] Electrolytic polishing process: A dual-tank electrolysis system is used; polishing solution ratio: 400-600 mL / L of 85% phosphoric acid and 200-300 mL / L of 98% sulfuric acid; electrolysis voltage 5-15V, electrolysis time 3-10 min.
[0065] The aforementioned polishing step can temporarily improve the surface finish of stainless steel sheets. Subsequent physical and chemical treatments can regulate and reduce surface roughness, and the effects of the two processes do not conflict. This polishing process aims to ensure the quality stability of the entire process. The mechanism of chemical etching treatment is as follows: it removes the passivation film on the stainless steel surface, while generating a surface layer rich in active hydroxyl and other polar groups, increasing the surface free energy, improving the wettability of the adhesive on the substrate surface; and it can provide more hydrogen bonding sites and chemical bonding sites for the polar functional groups of the adhesive, thereby strengthening the interfacial chemical adhesion effect.
[0066] The partitioned film formation process prepares an organic protective film resistant to hydrochloric acid through a photoreaction-enhanced film formation process; the organic protective film is an organosilicon-modified photocurable corrosion-resistant film, an epoxy-acrylic acid photocurable composite film, a nano-doped photocurable organic composite film, or a photoinitiated grafted fluorine-containing organic film.
[0067] In step S3, the first chemical treatment process includes the following steps:
[0068] Step S31, Degreasing and Cleaning: After the stainless steel sheet has been divided into sections and film-forming, it is ultrasonically cleaned with acetone and anhydrous ethanol for 5-15 minutes in sequence; after cleaning, it is placed in an electric heating constant temperature drying oven to dry at a temperature of 70±5℃.
[0069] Step S32: Prepare a hydrochloric acid etching solution containing hydrochloric acid and ferric chloride; select hydrochloric acid with a concentration of 36%-38%, add 20-100 mL / L of hydrochloric acid; add 100-250 g / L of ferric chloride;
[0070] Step S33, Chemical corrosion treatment: Immerse the degreased and dried stainless steel sheet in hydrochloric acid corrosion solution for the first corrosion treatment. The corrosion temperature is controlled at 20-40℃ and the corrosion time is 100-300min. After corrosion treatment, directional deep corrosion occurs on the lower side of the microstructure groove of the stainless steel sheet along the direction perpendicular to the wall thickness.
[0071] In step S4, the second chemical treatment process includes the following steps:
[0072] Step S41, Cleaning and Drying: Use acetone and anhydrous ethanol in sequence to ultrasonically clean the stainless steel sheet after the first chemical treatment process for 5-15 minutes, and after cleaning, place the stainless steel sheet in an electric constant temperature drying oven and dry it at 70±5℃.
[0073] Step S42: Prepare a mixed etching solution containing chromium trioxide and sulfuric acid; use concentrated sulfuric acid (H2SO4) with a concentration of 98%, add 150-400 mL / L, and add chromium trioxide (CrO3) with a concentration of 100-300 g / L.
[0074] Step S43, Secondary Corrosion: Immerse the stainless steel sheet after the first chemical treatment in the mixed corrosion solution and corrode it at 30-70℃ for 15-35 minutes.
[0075] In step S5, the stainless steel sheet after the second chemical treatment process is ultrasonically cleaned for 5-15 minutes using acetone and anhydrous ethanol in sequence; after cleaning, the stainless steel sheet is placed in an electric heating constant temperature drying oven to dry, and the drying temperature is controlled at 70±5℃.
[0076] In step S6, the vacuum bonding includes the following steps:
[0077] Step S61: Perform the first preforming on the stainless steel cladding sheet with microstructured grooves prepared by two chemical etching processes. Use a curved surface forming press to process the stainless steel cladding sheet so that the curvature of the stainless steel cladding sheet is less than the curvature of the surface to which the blade is bonded.
[0078] Step S62: Perform a second pre-forming on the stainless steel sheet. After forming, the curvature of the stainless steel sheet is greater than the curvature of the surface to which the blade is bonded. The stainless steel sheet is fixed by a vacuum chamber fixing fixture, and two welding pillars are welded to both sides of the outer surface. The two welding pillars are clamped by a vacuum motion fixture, so that the stainless steel sheet stores elastic potential energy.
[0079] Step S63: The vacuum coating robot applies adhesive A to the surface of the stainless steel sheet with chemically etched microstructure grooves in a vacuum environment.
[0080] Step S64: Another vacuum coating robot applies adhesive B to the surface of the blade to be bonded in a vacuum environment;
[0081] Step S65: The vacuum handling robot drives the blade displacement. The vacuum motion fixture drives the stainless steel sheet to move in space through two welded columns, releasing part of the elastic potential energy stored in the stainless steel sheet in advance, and completing the docking and bonding of the stainless steel sheet and the blade in a vacuum atmosphere.
[0082] Step S66: Keep the mixture warm and allow it to stand to fully cure the AB adhesive.
[0083] Step S67: Unload the material and remove the two welded pillars used for process clamping.
[0084] Example
[0085] See Figure 1 As shown, the stainless steel pretreated plate 1 includes a side 101, a mating surface 102, a bottom 103 of a microstructure groove, and a side wall of the microstructure groove. The side wall of the microstructure groove is divided into an upper part 104 and a lower part 105. The side wall between the mating surface 102 and the bottom 103 of the microstructure groove has the area near the mating surface 102 as the upper part 104 and the area near the bottom 103 as the lower part 105. The height of the side 101 of the stainless steel pretreated plate 1 is equal to the plate thickness. The mating surface 102 of the stainless steel pretreated plate 1 is provided with staggered microstructure grooves. In this embodiment, the depth-to-width ratio of the microstructure groove is between 4 and 5. For example, the microstructure depth is 0.96 and the width is 0.2, corresponding to a depth-to-width ratio of 4.8. The distance from the mating surface 102 to the bottom 103 of the microstructure groove is 0.96. Achieving sufficient wetting of adhesive in microstructured grooves with an aspect ratio greater than 4 is a technical challenge. This invention solves this problem by using a vacuum injection process.
[0086] Except for the lower part 104 on the side of the microstructure groove, the entire outer surface is photoreactively enhanced to form a hydrochloric acid-resistant organic coating protective film. The protective film can be, but is not limited to, an organosilicon-modified photocurable corrosion-resistant film, an epoxy-acrylic photocurable composite film, a nano-doped photocurable organic composite film, or a photo-initiated grafted fluorine-containing organic film. The photoreactive enhanced film formation can be achieved using mature coating processes such as vapor deposition, ultraviolet irradiation, photoorganic crosslinking reaction, and mask removal.
[0087] See Figure 2 and Figure 3 As shown, stainless steel pretreated plate 1 undergoes a first chemical etching treatment to obtain stainless steel chemically etched plate 2. Stainless steel chemically etched plate 2 includes an etched material side 201, a bonding etched material surface 202, a bottom etched material microstructure groove 203, an upper part etched material microstructure groove side 204, and a lower part etched material microstructure groove side 205. Compared to the lower part 105 of the microstructure groove side of the original stainless steel pretreated plate 1, the lower part 205 of the microstructure groove side of the stainless steel chemically etched plate 2 has a certain depth removed by etching along a direction perpendicular to the sidewall.
[0088] The stainless steel chemically etched sheet 2 is subjected to a second chemical treatment and final cleaning and drying to obtain a stainless steel cladding sheet 8 with a microstructure groove of secondary chemical corrosion.
[0089] See Figure 4 As shown, the stainless steel sheet 8, which has been prepared with microstructured grooves through two chemical etching processes, undergoes a first pre-forming process using a curved surface forming press to ensure that the curvature of the stainless steel sheet 8 is less than the curvature of the surface to which the blade 4 is bonded. The stainless steel sheet 8 undergoes a second pre-forming process, after which the curvature of the stainless steel sheet 8 is greater than the curvature of the surface to which the blade 4 is bonded. The stainless steel sheet 8 is fixed by a vacuum chamber fixing fixture 5, and a first welding column 6 and a second welding column 7 are welded to both sides of its outer surface. The first welding column 6 and the second welding column 7 are clamped by a vacuum motion fixture, allowing the stainless steel sheet 8 to store elastic potential energy. In a vacuum environment, a vacuum coating robot applies adhesive A to the surface of the stainless steel sheet 8, which has chemically etched microstructure grooves. Simultaneously, another vacuum coating robot applies adhesive B to the surface of the blade 4 to be bonded in a vacuum environment. Subsequently, a vacuum handling robot drives the blade 4 to move, and the vacuum motion fixture drives the first welding column 6 and the second welding column 7 to perform spatial movement, releasing part of the elastic potential energy pre-stored in the stainless steel sheet 8, and completing the bonding of the two in a vacuum atmosphere. After bonding, the sheet is kept at a constant temperature to allow the AB adhesive to fully cure. Finally, the unloading operation is performed, and the first welding column 6 and the second welding column 7 used for process clamping are removed.
[0090] Figure 5 This is a three-dimensional schematic diagram of the structure after bonding; Figure 7 This is an exploded view of the structure after bonding. Figure 8 This is an exploded view of the bonded structure from another angle; the diagram includes the stainless steel sheath 8, the cured adhesive layer 3, and the blade 4. This bonded structure features a spatial T-groove locking characteristic. Constructing precise microstructure grooves on the surface of the stainless steel sheath 8 significantly improves interfacial bonding performance. By designing regularly spaced microstructure grooves, the adhesive forms a three-dimensional interlocking mechanism with the microstructure grooves during curing. When the stainless steel sheath 8 and the substrate of the blade 4 experience relative displacement, the protrusions at the edge of the adhesive grooves mechanically engage with the adhesive, effectively resisting shear stress and preventing interfacial slippage failure. Simultaneously, these microstructure grooves guide the directional flow of the adhesive, significantly improving wettability and ensuring the adhesive spreads evenly and adheres tightly to the surface of the stainless steel sheath 8. This optimized interfacial contact effectively eliminates defects such as bubbles and voids, forming a highly dense bonding interface, thereby comprehensively improving the reliability and durability of the connection.
[0091] Figure 8Experimental diagrams showing the contact angles of stainless steel sheets with different surface morphologies and liquids: (a) Original smooth flat sample, liquid contact angle 74.6±4.2°; (b) Microstructure sample with a groove width of 0.1 mm, liquid contact angle 64.4±3.9°; (c) Microstructure sample with a groove width of 0.2 mm, liquid contact angle 64.7±3.6°; (d) Microstructure sample with a groove width of 0.1 mm after chemical etching, liquid contact angle 31.1±2.6°; (e) Microstructure sample with a groove width of 0.2 mm after chemical etching, liquid contact angle 26.8±2.2°. The test results show that creating microstructure grooves on the stainless steel surface can reduce the liquid contact angle and improve the adhesive wetting ability, which is beneficial to improving the bonding effect. Microstructure grooves combined with chemical etching treatment can further reduce the contact angle and optimize the interface wetting state. The wettability (e.g., hydrophilicity or hydrophobicity) of metal surfaces directly affects their coating, bonding, and corrosion protection properties. Chemical etching, as a surface treatment method, can improve wettability by altering the microstructure and chemical composition of metal surfaces through controlled chemical reactions. In the bonding of helicopter rotor blade cladding, good wettability enhances the spreading and adhesion of adhesives or coatings to metal surfaces. This group of experiments confirms that the combined process of microstructured groove fabrication and chemical etching can effectively improve the adhesion between stainless steel and rotor blades.
[0092] This invention combines roll forming with chemical etching. First, the stainless steel sheet is roll-formed to form a uniformly distributed grid on the inner side of the sheet. Then, chemical etching is performed to improve the wettability of the metal surface, thereby increasing the bonding strength of the blade leading edge protective sheet. This solves the problem of easy delamination of the leading edge metal cladding that is common in helicopter composite rotor blades. The improvement of the stainless steel cladding not only enhances aviation safety but also reduces equipment maintenance costs and extends the service life of components.
[0093] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A process for improving the bonding strength of stainless steel cladding on the leading edge of a propeller blade, characterized in that, Includes the following steps: Step S1: Prepare microstructured grooves on the surface of stainless steel sheet; Step S2, billet pretreatment and partitioned film formation: the stainless steel sheet is polished, and then an acid-resistant organic protective film is prepared on the upper side of the microstructure groove and the rest of the surface of the stainless steel sheet, exposing the lower side of the microstructure groove. Step S3, First chemical treatment: After cleaning and drying, selective corrosion is carried out using hydrochloric acid etching solution to form a deep corrosion area on the lower side of the microstructure tank. Step S4, Second Chemical Treatment: A mixed etching solution is used for secondary etching treatment to remove the organic protective film on the surface of the stainless steel plate. Step S5, Final Cleaning: Ultrasonic cleaning with a combination of organic solvents and drying are used to obtain a stainless steel sheet with a microstructure groove with secondary chemical corrosion. Step S6, Vacuum bonding: The stainless steel sheet is pre-formed twice with different curvatures to store elastic potential energy. Two-component adhesive is applied to the bonding surfaces of the stainless steel sheet and the carbon fiber blade in a vacuum environment. The sheets are then elastically reset, tightly bonded and cured to form a spatial T-shaped locking bonding structure.
2. The process method for improving the bonding strength of the stainless steel cladding at the leading edge of the blade according to claim 1, characterized in that, In step S1, the microstructure grooves on the bonding surface of the stainless steel sheet are square array mesh microstructures, the depth of the mesh microstructure is 0.1-0.4mm, the side length of a single square mesh is 0.3-0.6mm, and the mesh spacing is 0.1-0.2mm; The mesh microstructure is formed by rolling with upper and lower paired molds. The bottom of the upper mold is provided with a square array of bosses, and the lower mold supports the stainless steel plate.
3. The process method for improving the bonding strength of the stainless steel cladding at the leading edge of the blade according to claim 1, characterized in that, In step S2, the partitioned film formation process prepares an organic protective film resistant to hydrochloric acid through a photoreaction-enhanced film formation process; the organic protective film is an organosilicon-modified photocurable corrosion-resistant film, an epoxy acrylic photocurable composite film, a nano-doped photocurable organic composite film, or a photoinitiated grafted fluorine-containing organic film.
4. The process method for improving the bonding strength of the stainless steel cladding at the leading edge of the blade according to claim 1, characterized in that, In step S3, the first chemical treatment process includes the following steps: Step S31, Degreasing and Cleaning: After the stainless steel sheet has been divided into sections and film-forming, it is ultrasonically cleaned with acetone and anhydrous ethanol for 5-15 minutes in sequence; after cleaning, it is placed in an electric heating constant temperature drying oven to dry at a temperature of 70±5℃. Step S32: Prepare a hydrochloric acid etching solution containing hydrochloric acid and ferric chloride; Step S33, Chemical corrosion treatment: Immerse the degreased and dried stainless steel sheet in hydrochloric acid corrosion solution for corrosion. The corrosion temperature is controlled at 20-40℃ and the corrosion time is 100-300min. After corrosion treatment, directional deep corrosion occurs on the lower side of the microstructure groove of the stainless steel sheet along the direction perpendicular to the wall thickness.
5. The process method for improving the bonding strength of the stainless steel cladding at the leading edge of the blade according to claim 4, characterized in that, In step S32, a hydrochloric acid etching solution containing hydrochloric acid and ferric chloride is prepared. The hydrochloric acid with a concentration of 36%-38% is selected, and the amount of hydrochloric acid added is 20-100 mL / L; the amount of ferric chloride added is 100-250 g / L.
6. The process method for improving the bonding strength of the stainless steel cladding at the leading edge of the blade according to claim 1, characterized in that, In step S4, the second chemical treatment process includes the following steps: Step S41, Cleaning and Drying: Use acetone and anhydrous ethanol in sequence to ultrasonically clean the stainless steel plate after the first chemical treatment process for 5-15 minutes, and dry it at 70±5℃. Step S42: Prepare a mixed etching solution containing chromium trioxide and sulfuric acid; Step S43, Secondary Corrosion: Immerse the stainless steel sheet after the first chemical treatment in the mixed corrosion solution and corrode it at 30-70℃ for 15-35 minutes.
7. The process method for improving the bonding strength of the stainless steel cladding at the leading edge of the blade according to claim 6, characterized in that, In step S42, a mixed etching solution containing chromium trioxide and sulfuric acid is prepared. Concentrated sulfuric acid with a concentration of 98% is selected and added at a rate of 150-400 mL / L. The amount of chromium trioxide added is 100-300 g / L.
8. The process method for improving the bonding strength of the stainless steel cladding at the leading edge of the blade according to claim 1, characterized in that, In step S5, the stainless steel sheet after the second chemical treatment process is ultrasonically cleaned for 5-15 minutes using acetone and anhydrous ethanol in sequence; after cleaning, the stainless steel sheet is placed in an electric heating constant temperature drying oven to dry, and the drying temperature is controlled at 70±5℃.
9. The process method for improving the bonding strength of the stainless steel cladding at the leading edge of the blade according to claim 1, characterized in that, In step S6, the vacuum bonding includes the following steps: Step S61: Perform the first preforming on the stainless steel cladding sheet that has been prepared with microstructured grooves through two chemical etching processes, so that the curvature of the stainless steel cladding sheet is less than the curvature of the surface to which the blade is bonded. Step S62: Perform a second pre-forming on the stainless steel sheet. After forming, the curvature of the stainless steel sheet is greater than the curvature of the surface to which the blade is bonded. The stainless steel sheet is fixed by a vacuum chamber fixing fixture, and two welding pillars are welded to both sides of the outer surface. The two welding pillars are clamped by a vacuum motion fixture, so that the stainless steel sheet stores elastic potential energy. Step S63: The vacuum coating robot applies adhesive A to the surface of the stainless steel sheet with chemically etched microstructure grooves in a vacuum environment. Step S64: Another vacuum coating robot applies adhesive B to the surface of the blade to be bonded in a vacuum environment; Step S65: The vacuum handling robot drives the blade displacement. The vacuum motion fixture drives the stainless steel sheet to move in space through two welded columns, releasing part of the elastic potential energy stored in the stainless steel sheet in advance, and completing the docking and bonding of the stainless steel sheet and the blade in a vacuum atmosphere. Step S66: Keep the mixture warm and allow it to stand to fully cure the AB adhesive. Step S67: Unload the material and remove the two welded pillars used for process clamping.
Citation Information
Patent Citations
Treatment method for titanium alloy covered edge of helicopter blade
CN112846674A